The Impact of Teaching Vocabulary for Junior High School Students Using Scrabble Game - sulaiman, sulaiman (International Journal of English Education and Linguistics (IJoEEL), 2019)
ABSTRACTThis research aimed to investigate the use of teaching vocabulary using Scrabble Game on the students’ achievement. The method applied in this research is Pre-experimental research. Pre-experimental research use three group Pre-test and Post-test. The sample of this research is the first grade students of SMP Negeri 1 sungai Raya Kepulauan.The experimental group was given a pre-test consisted 20 items of test (that was initially tried out before at the same class). After the Pre-test was done, it was continued with three times of treatments where the researcher used 20 words as the screabble material, antonym and synonym words. After the treatments were given, a Post-test with the same test items was administered. The result of Pre-test and Post-test were calculated and compared to determine significant increase by using the matched t-test formula. The research finding the t observed value is 3.66 indicated that the treatments have an effect on performance. Since the value of the observed t value is 3.66 exceeds the t critical value of 2.262 at the intersection of 9 df and .05, it shows that the students’ scores differ significantly from Pre-test to Post-test. This research shows that teaching vocabulary using scrabble game increases the students’ achievement onvocabulary. Scrabble game is basically suggested and considered good and appropriate as technique at teaching vocabulary.Keywords : scrabble game, vocabulary, pre experimental.